Design of metadata elements for digital news articles in the omnipaper project - Yaginuma, T. (2003)
This paper examines and proposes a set of metadata elements for describing digital news articles for the benefit of distributed and heterogeneous news resource discovery. Existing digital news description standards such as NITF and NewsML are analysed and compared with Dublin Core Metadata Element Set (DCMES), which results in that the use of Dublin Core is encouraged for interoperability of the resources. The suggested metadata elements are carefully selected and defined considering the characteristics of news articles. Some elements are detailed with refinement qualifiers and recommended encoding scheme. This set of metadata has been developed as a part of the tasks in the IST (Information Society Technologies)-funded European project OmniPaper (Smart Access to European Newspapers, IST-2001-32174).